2002
DOI: 10.1007/s00280-002-0489-4
|View full text |Cite
|
Sign up to set email alerts
|

Phage-displayed random peptide libraries in mice: toxicity after serial panning

Abstract: Serial administration of an RPL is well tolerated and serial panning in individual mice leading to consensus sequence motifs is possible. Based on these preclinical data the Food and Drug Administration has approved the implementation of human clinical trials with this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…The complexities of the random 12-and 20-mer libraries were 1.26 Â 10 7 and 1.8 Â 10 7 different peptides, respectively. The details of library preparation, titration, elution of cell-bound phage, phage plating, and amplification have been described in detail in our earlier publications (19,32,34,35).…”
Section: Phage Librariesmentioning
confidence: 99%
See 3 more Smart Citations
“…The complexities of the random 12-and 20-mer libraries were 1.26 Â 10 7 and 1.8 Â 10 7 different peptides, respectively. The details of library preparation, titration, elution of cell-bound phage, phage plating, and amplification have been described in detail in our earlier publications (19,32,34,35).…”
Section: Phage Librariesmentioning
confidence: 99%
“…This was carried out using an ELISA-based method developed and used in our preclinical study (32). Briefly, a 96-well polystyrene microplate (F96 Maxisorb Immuno plate, Nulge Nunc, Roskilde, Denmark) was coated with 1 Â 10 7 transducing units (TU) of filamentous phage ( from phage library) overnight at 4jC.…”
Section: Estimation Of Serum Phage Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…After demonstrating minimal toxicity during in vivo screening of phage-displayed peptide libraries in mice, another group received FDA approval for the use of the technique in human clinical trials [74]. Krag et al reported the results of a Phase I clinical trial in 2006 in which eight stage IV cancer patients received intravenous infusions of filamentous phage-displayed peptide or single-chain antibody libraries [75].…”
Section: Potential Target-specific Peptides Identified Using Phage-dimentioning
confidence: 99%